American Hegemony and China-Russia Entente Cordiale - Dr Shahid Hameed (CISS Insight Journal, 2023)
The American unipolar hegemony over global order has begun flickering in just a decade after the Soviet Union’s dissolution. Russia has resurged and China has risen, and an informal alliance has emerged between the two against the American-led axis to contain both powers. China and Russia have not been natural allies, but a joint threat is fusing their common interests. The so-called Global War on Terror was a phase that profoundly altered global politics and led China and Russia to two broad common objectives i.e., rationalize US-led world order and fragment unipolarity into controlled regions. China is played as the primary and Russia as the secondary bogey to Western dominated global order, but the reality may be different. Status quo in the international order suits the US because addressing Russian “will” and so-called “offensive character” are ostensibly a bigger challenge than containing China. This paper offers an analysis that the US faces a bigger challenge to curtail Russian objective of building controlled regions than containing China’s economic and strategic maneuvers. Russian and Chinese grand strategies to rationalize global order have some congruent and independent objectives.